1997
DOI: 10.1128/jcm.35.4.988-991.1997
|View full text |Cite
|
Sign up to set email alerts
|

False-positive results from cultures of Mycobacterium tuberculosis due to laboratory cross-contamination confirmed by restriction fragment length polymorphism

Abstract: During 1994, a cross-contamination problem leading to false-positive cultures of Mycobacterium tuberculosis was revealed in a mycobacteriology laboratory processing 30,000 to 35,000 samples per year. Molecular strain typing based on restriction fragment length polymorphism confirmed the contaminations. Out of 1,439 positive cultures of Mycobacterium tuberculosis, 49 samples from 48 patients were suspected to be cross-contaminated. In 37 cases, growth was observed both in BACTEC vials and on solid media, indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 15 publications
1
16
0
1
Order By: Relevance
“…Confirmation of suspected cross contamination of specimens in mycobacteriology laboratories by molecular biology-based techniques has been reported previously (4,27,39). Our study reports that cultures for 24 (7.8%) patients were found to be falsely positive, and for 13 of these patients, the contamination was not suspected before strain fingerprinting.…”
Section: Discussionsupporting
confidence: 79%
“…Confirmation of suspected cross contamination of specimens in mycobacteriology laboratories by molecular biology-based techniques has been reported previously (4,27,39). Our study reports that cultures for 24 (7.8%) patients were found to be falsely positive, and for 13 of these patients, the contamination was not suspected before strain fingerprinting.…”
Section: Discussionsupporting
confidence: 79%
“…These errors can lead to unnecessary visits of falsely diagnosed patients to medical consultants and unnecessary long‐term antimicrobial treatment. Since the introduction of accurate strain typing methods, it has become clear that sampling and laboratory errors occur more frequently than previously assumed [240–245]. Small et al .…”
Section: Use Of Dna Fingerprinting To Detect Laboratory Cross‐contamimentioning
confidence: 99%
“…The stability and reproducibility of the technique as well as its usefulness in epidemiological studies has been convincingly demonstrated (8,16,17), and new insight into the nature of tuberculosis (TB) transmission has been obtained. Furthermore, RFLP has become an indispensable tool for quality assurance of the processing and culturing of patient samples, since it offers an opportunity to verify suspected cases of crosscontamination (2,13).…”
mentioning
confidence: 99%